The relationship between investment interest and entrepreneurial interest on financial intelligence among Bengkulu University students - Kristian Simbolon; Intan Zoraya (Jurnal Mantik, 2023)
The government emphasizes the importance of an entrepreneurial spirit and investing in educational institutions, to produce skilled and financially intelligent graduates. With this spirit, it is hoped that university graduates will change from job seekers to job creators. This research aims to determine the relationship between interest in investing and interest in entrepreneurship on the level of financial intelligence of Bengkulu University students. The research method used is quantitative research using primary data. The research population was students from the economics faculty at Bengkulu University, and the sample used was 150 data. Data analysis was carried out using multiple regression analysis methods. The research results show that H1 is accepted, while H0 is rejected, which indicates that both Investment Interest (X1) and Entrepreneurial Interest (X2) jointly influence the level of Financial Intelligence (Y). Furthermore, based on calculations, it is known that the variables Investment Interest (X1) and Entrepreneurial Interest (X2), together, contribute 69.9% to the level of Financial Intelligence (Y). The remaining 30.1% is influenced by other factors that have not been investigated in this research